Minimally Invasive Retropleural Thoracic Diskectomy: Step-by-Step Operative Planning, Execution, and Results. Issue 4 (11th October 2022) - Farber, S. Harrison; Xu, David S.; Walker, Corey T.; Godzik, Jakub; Turner, Jay D.; Uribe, Juan S.
Abstract : BACKGROUND: Thoracic disk herniation is rare and difficult to treat. The minimally invasive lateral retropleural approach to the thoracic spine enables the surgeon to decompress the neural elements and minimize thecal sac manipulation through direct visualization with less exposure-related morbidity. OBJECTIVE: To provide a detailed step-by-step overview of the minimally invasive retropleural approach for thoracic diskectomies, including preoperative planning through postoperative care as practiced at our institution. METHODS: Lateral retropleural thoracic diskectomies performed at a single institution from July 1, 2017, to June 30, 2020, were reviewed. Clinical and outcome data were collected and analyzed. The retropleural approach was divided into several components: relevant anatomy, indications and contraindications, preoperative setup, exposure and approach, diskectomy, and closure and postoperative care. RESULTS: Twelve patients were treated during the study interval. Their average (SD) age was 44.2 (9.5) years; 10 of 12 were men. Eleven patients presented with thoracic myelopathy. The level treated ranged from T6-7 to T12-L1. Disk herniations were calcified in 10 of 12 patients. These lesions were approached from the left side in 7 of 12 patients. Six patients had complications, none of which were neurological. Chest tubes were placed for pleural violation, pneumothorax, or hemothorax in 3 patients. Two patients experienced postoperative abdominal pseudohernia. Neurological symptoms were stable or improved in all patients. The median (IQR) Nurick scale improved from 3.0 (2.0-3.0) preoperatively to 1.0 (0-3.0) ( P = .026) postoperatively. CONCLUSION: Lateral retropleural diskectomy enables safe, efficient resection of most thoracic disks while minimizing patient morbidity.